Expert evaluation of criteria describing the quality of travelling by international passenger train: technological, economic and safety perspectives - Maskeliūnaitė, Lijana; Sivilevičius, Henrikas (Technological and Economic Development of Economy, 2012)
The goals, needs and possibilities of interested parties (administration, service staff and passengers travelling in a train) should be taken into account when organizing passenger transportation and making decisions concerning particularly this area. Improvement in passenger transportation (train travel) depends on experience, qualification and decisions made by the experts involved in this process. The paper analyses the performance of the joint-stock company Lietuvos geležinkeliai and examines criteria describing the quality of passenger transportation provided by this organization. The article presents the methods for showing the consistency of respondent and expert judgements on ranking the sets of criteria defining the quality of travelling by train. The significance of the considered criteria is based on a pair wise comparison. The employed method allows for determining the normalized weights of particular criteria with respect to other criteria of the analysed group (A, B, C, D). The article offers an algorithm for displaying the quality of train travel. The ranks assigned to the criteria by train passengers (category K), service staff (category P) and administrative staff (category A) are calculated establishing the differences between the ranks of criteria. The opinions of the respondents and experts belonging to categories K, P and A are compared considering the significance of the adopted criteria. The paper provides the results obtained from the surveyed respondents and experts and presents the ranks given to criterion groups A, B, C, D describing the quality of train travel. Finally, the conclusions based on the performed research are presented.